Comparative Evaluation of the Effects of Conservation Agriculture Integrated with Various Land Management Practices on Vertisol Productivity in Highlands of Ethiopia - Mitiku, Getacher Kassa; Woldemariam, Ayele Desalegn; Abebe, Tilahun Getachew; Atilaw, Kebede Bekele; Yilma, Temesgen; Getaneh, Lisanu (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Vertisols are dark-colored clays that develop cracks when it expands and contracts with changes in moisture content. Tillage techniques and frequency have an impact on crop harvesting, drainage, soil erosion, moisture conservation, and weeding in Ethiopia's highlands. Five tillage methods, namely, broad bed and furrows (BBF), permanently raised bed with no-tillage (PRB+NT), permanently raised bed with no-tillage, and 30% stubble retention (PRB+NT+M), flatbed with no-tillage (Flat+NT), and flatbed with no-tillage and 30% stubble retention (Flat+NT+M), were evaluated for their effects on the productivity of vertisol. This study was conducted in Moretna Jiru wereda, Enewari, for seven years (2015 to 2022) in the central highlands of Ethiopia. In this study, soil indicators such as moisture content, bulk density, organic carbon, pH, available phosphorus, extractable potassium, electrical conductivity, and total nitrogen, as well as productivity indicators such as plant height, grain yield, and straw yield, were measured. The results indicated that Flat+NT+M and Flat+NT significantly increased wheat grain yield by 13.4% and 11.2%, respectively compared with BBF, for the experimental years 2015/16 and 2017/18. In the experimental years 2019/20 and 2021/22, the wheat yield was greater under BBF than conservation agriculture practices. Compared with conservation agriculture practices, BBF resulted in the highest grain yield of faba bean. The soil property data imply that PRB+NT+M, Flat+NT, and Flat+NT+M improved the total nitrogen, soil pH, organic carbon, moisture holding capacity, and extractable potassium. Economically, Flat+NT was the most profitable practice, with an 1147.6% marginal rate of return (MRR). Based on the results, Flat+NT and Flat+NT+M are beneficial for wheat production during dry years, while BBF is beneficial for fababean production.